Cluster evolution and urban industrial dynamics in the transition from a planned to a socialist market economy: the case of Beijing. Issue 1 (2nd January 2017) - Yang, Zhenshan; Dunford, Michael
ABSTRACT: Cluster evolution and urban industrial dynamics in the transition from a planned to a socialist market economy: the case of Beijing. Spatial Economic Analysis . The transformation of the industrial structure of Beijing in the transition from a planned to a socialist market economy integrated into global markets is examined through the lens of cluster evolutions and life cycles in 1987–2007. Cluster emergence, decomposition, stabilization, upgrading, restructuring and disappearance are identified using exploratory factor analysis of input–output tables. These evolutions are interpreted in the light of the way in which backward and forward linkages provide channels of communication, new intermediate goods, new divisions of labour and new patterns of co-location, and are related to the changing industrial geography of Beijing.